An in vitro analysis of an innovative standardized phospholipid carrier-based Melissa officinalis L. extract as a potential neuromodulator for emotional distress and related conditions - Kara, Mehtap; Sahin, Sumeyye; Rabbani, Fazle; Oztas, Ezgi; Hasbal-Celikok, Gozde; Kanımdan, Ebru; Kocyigit, Abdurrahim; Kanwal, Ayesha; Wade, Ursula; Yakunina, Anastasia; Di Pierro, Francesco; Khan, Amjad (Frontiers in Molecular Biosciences, 2024)
Background:Melissa officinalis L. (MO), commonly known as lemon balm, a member of the mint family, is considered a calming herb. In various traditional medicines, it has been utilized to reduce stress and anxiety and promote sleep. A growing body of clinical evidence suggests that MO leaf extract supplementation possesses considerable neuropharmacological properties. However, its possible mechanism of action largely remains unknown. Objective: In the present in vitro studies, we comparatively investigated the central nervous system (CNS)-calming and antioxidative stress properties of an innovative standardized phospholipid carrier-based (Phytosome™) MO extract (Relissa™) vs. an unformulated dry MO extract. Methods: The neuropharmacological effect of the extract was studied in the anti-depressant enzymes γ-aminobutyrate transaminase (GABA-T) and monoamine oxidase A (MAO-A) assays and SH-SY5Y cells brain-derived neurotrophic factor (BDNF) expression assay. The neuroprotective effect of the extract against oxidative stress was assessed in SH-SY5Y cell-based (H2O2-exposed) Total Antioxidant Status (TAS) and Total Reactive Oxygen Species (ROS) assays. The cytotoxic effect of the extract was evaluated using MTT and LDH assays. The extract antioxidant effect was also evaluated in cell-free chemical tests, including TEAC-ABTS, DPPH, Ferric Reducing Antioxidant Power (FRAP), Oxygen Radical Antioxidant Capacity (ORAC), and Hydroxyl Radical Antioxidant Capacity (HORAC) assays. Results: Relissa™ exhibited high GABA-T inhibitory activity, IC50 (mg/mL) = 0.064 vs. unformulated dry MO extract, IC50 (mg/mL) = 0.27. Similar inhibitory effects were also observed for MAO-A. Relissa™ demonstrated an improved neuroprotective antioxidant effect on SH-SY5Y cells against H2O2-induced oxidative stress. Compared to unformulated dry MO extract, Relissa™ exerted high protective effect on H2O2-exposed SH-SY5Y cells, leading to higher cells BDNF expression levels. Moreover, cell-free chemical tests, including TEAC-ABTS, DPPH radical scavenging, FRAP, ORAC, and HORAC assays, validated the improved antioxidant effect of Relissa™ vs. unformulated dry MO extract. Conclusion: The results of the present study support the neuromodulating and neuroprotective properties of Relissa™, and its supplementation may help in the amelioration of emotional distress and related conditions.